2013
DOI: 10.1242/jcs.136648
|View full text |Cite
|
Sign up to set email alerts
|

Sharp-1 regulates TGF-β signaling and skeletal muscle regeneration

Abstract: Sharp-1 is a basic helix-loop-helix (bHLH) transcriptional repressor that is involved in a number of cellular processes. Our previous studies have demonstrated that Sharp-1 is a negative regulator of skeletal myogenesis and it blocks differentiation of muscle precursor cells by modulating the activity of MyoD. In order to understand its role in pre-and post-natal myogenesis, we assessed skeletal muscle development and freeze-injury-induced regeneration in Sharp-1-deficient mice. We show that embryonic skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Laminin and collagen IV are major components of the basement membrane, which constitutes one side of the satellite cell niche as well as serving to surround—mechanically support—muscle fibers. The proteoglycan decorin has been shown to play a role in inducing the proliferation of satellite cells (14) and in modulating fibrosis in regenerating muscle (13). Transient fibrosis is often seen during regeneration (28), the removal of which is important for the completion of the restoration process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laminin and collagen IV are major components of the basement membrane, which constitutes one side of the satellite cell niche as well as serving to surround—mechanically support—muscle fibers. The proteoglycan decorin has been shown to play a role in inducing the proliferation of satellite cells (14) and in modulating fibrosis in regenerating muscle (13). Transient fibrosis is often seen during regeneration (28), the removal of which is important for the completion of the restoration process.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the potential of NSAIDs to influence muscle ECM remodeling is unknown. In the current study, we chose to focus on these same groups of matrix proteins and also to include decorin, which has been shown to play a role in modulating fibrosis (13) as well as in activating satellite cells (14).…”
mentioning
confidence: 99%
“…Furthermore, DE miRNAs were intensively involved in not only the metabolic pathways such as lipid metabolic process, fatty acid metabolic process, galactose metabolism, cysteine and methionine metabolism but also signaling pathways such as wnt-protein binding, toll-like receptor, mTOR, TGF-β, positive regulation of MAPK cascade signaling pathways ( Fig 6 ). Many studies have reported that the TGF-β family played important roles in skeletal muscle development [ 35 , 36 ]. MAPK signalling pathway is known to be involved in regulation of muscle differentiation by affecting the activities of myogenic transcription factors as well as controlling the expression of structural muscle genes [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α pushes cells toward apoptosis, whereas the TGFs appear to direct them towards fibrosis [ 1 ]. TGF-β plays a key role in the fibrogenic response of skeletal muscle after CCl 4 treatment [ 23 , 24 , 25 , 26 ] . We found that not only liver but also skeletal muscle is impaired by chronic CCl 4 intoxication.…”
Section: Discussionmentioning
confidence: 99%